Molecular weight impact on the mechanical forces between hyaluronan and its receptor. (1st October 2018) - Jiang, Lei; Liu, Guihua; Liu, Hanyun; Han, Juan; Liu, Zhibin; Ma, Hongchao
Graphical abstract: Highlights: Lateral and normal forces were measured between hyaluronan (HA) and receptor CD44. HA-CD44 binding depends on HA molecular weight (MW). Impact of HA multivalency is more than the sum of separate monovalent bindings. High friction patches were observed on frictional force microscopy. High friction patches may be due to HA-induced CD44 protein clustering. Abstract: Hyaluronan (HA) possesses manifold mechanical and signaling properties in the body. Most of these activities are largely regulated by its molecular weight, which often triggers opposing functions. However the molecular basis for such function distinction between HA size categories remains unclear. Using a combination of biophysical techniques, we measured the physical forces between HA ligand and its specific receptor CD44 in both normal and lateral directions, at different HA molecular weights and bound states. It was found that the impact of HA multivalency is more than just the sum of separate monovalent bindings. The HA-CD44 specific interaction enhances with HA molecular weight and the maximum binding occurs at ∼1000 kD, possibly due to the balance between multivalent HA zipping effect and conformational entropy. High friction patches, probably from CD44 protein clustering, was observed in friction force microscopy (FFM) upon HA shearing, which is also dependent on HA molecular weight. These results could help to understand the biophysical mechanism of HA in regulating CD44-induced physiological activities and thus facilitate the new design of HA-based material in fine tuning the receptor responses.